Challenges of Implementing Agile Methodology in the Jordanian Banking Sector - Alaraj, Abdal Hafeth (European Scientific Journal, ESJ, 2025)
Traditional banking operations must be changed because financial industry dynamics and customer demands have started to transform the market. Financial institutions use Agile methods which were created for software development to increase operational efficiency while boosting customer satisfaction levels. Multiple challenges persist for Jordanian banks when they attempt to implement Agile methodologies. The main obstacle stems from employees who resist change. Regulatory demands together with the intricate nature of system integration prove to be big obstacles for organizations. Several banking institutions across the industry encounter difficulties due to limited Agile proficiency among their staff. The implementation process faces various barriers because of workplace hierarchy structures. This research combines interviews with banking experts and surveys to study Agile implementation in Jordanian banks through a mixed-methods approach. The study identifies important barriers that lead to proposed solutions including professional training for selected positions as well as top-level executive backing and stepwise rollouts. The solutions to these problems will enable Jordanian banks to gain agility and competitiveness as well as innovation potential. The study advances knowledge about Agile adoption in literature while presenting usable recommendations for financial institutions. Survey results show resistance to change was the highest barrier at 75% of Jordanian banking employees, then followed by insufficient training as the highest issue at 50%. Moreover, 45% of the participants struggled to implement Agile with existing banking systems​. These remarks highlight formal Agile transformation approaches, including specialized training programs and executive-level sponsorship.